What drives consumers’ intention towards fairness-oriented products purchasing? An emotion-extended model of theory of planned behaviour - Antonella Samoggia; Giulia Rossi; Andrea Fantini; Evangelia Mouchtaropoulou; Notis Argiriou (Heliyon, 2025)
Fairness-oriented products have attracted increased interest in the last few years, particularly within the context of agrifood systems. However, in scholarly literature, limited studies are available where researchers discuss what drives consumers' choices towards fair food. This study investigates consumers’ purchasing intentions towards fairness-oriented food products by applying an emotion-extended model of the Theory of Planned Behaviour (TPB). Building upon TPB, the research incorporates emotions and price perception as additional variables to understand consumers' attitudes, subjective norms, and perceived behavioral control towards fairness-oriented food products. Data collection includes a survey carried out with a convenience sample of 294 Italian consumers. Data elaboration includes a Structural Equation Modeling to explore the complex relationships between the extended TPB constructs and their influence on consumer purchasing intentions. The findings reveal the significant impacts of emotions on attitudes and subjective norms, therefore highlighting its indirect effect on consumers' intentions. Attitude and subjective norms emerged as the main direct drivers of intention to purchase fairness-oriented food products, while perceived behavioral control and price perception showed no significant impact. Furthermore, the study applied an ANOVA analysis to identify sociodemographic differences, indicating varied perceptions and beliefs among different age groups, educational levels, and those valuing fairtrade labels. The value of current research aims at understanding how consumers perceive fairness throughout the agrifood chain. In addition, it provides valuable managerial insights, highlighting the role of emotions in shaping consumer intentions towards ethical behavior.